Study of cytotoxic activities of Rubraxanthone - Bakhtiar, M. Taher; Sawaneh, Fatoumata; Darnis, Deny Susanti (2009)
Rubraxanthone is a prenylated xanthone that was isolated from Garcinia euginifolia (Guttiferae). It is having antimicrobial and antiplatelet activating factor activities. The research is aimed to study a cytotoxic activity of the compound by using in vitro cell culture technique. In order to evaluate the activity against cancer, the compound is exposed for its activity against several cancerous cell lines. It is tested against breast (MCF-7), bone (Saos-2), cervix (SiHa and C33A), colorectal (HCT-116), esophageal (TE1 and TE2), rectum (SW837) cancer cells and normal fibroblast (NHDF). The cells were seeded in a 96-well plate a density of 2 x 10^5 cells/mL. The compound is being tested to confluent celss for two days. Antiproliverative activity is evaluated by 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazoliumbromide) (MTT) assay. It is found that the compound exhibits a moderate activity against all type of the cells.